2011
DOI: 10.1080/09670262.2011.565128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and irradiance on growth of strains belonging to sevenSkeletonemaspecies isolated from Dokai Bay, southern Japan

Abstract: The effect of temperature on the growth of Skeletonema ardens, S. costatum sensu stricto, the S. marinoi-dohrnii complex, S. japonicum, S. menzelii, S. pseudocostatum and S. tropicum isolated from Dokai Bay in southern Japan were examined under five to seven different temperatures and an irradiance of 150 mmol m À2 s À1. The effect of irradiance on the growth of the seven Skeletonema species was also examined under a wide range of irradiances ranging from 7-700 mmol m À2 s À1 at 20 C. AllSkeletonema species we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
3
33
0
1
Order By: Relevance
“…Temperature is thought to influence phytoplankton species richness and diversity (Graham et al 2004), in part because temperature strongly influences the growth rates of individual species (Thomas et al 2012), including those in the genus Skeletonema. A comparison of growth rates under different temperatures revealed that cultures of S. marinoi grew faster than other Skeletonema species at the lowest tested temperatures (10 and 15°C) (Kaeriyama et al 2011). This could explain the dominance of S. marinoi in winter-spring samples, although wintertime temperatures in NBay drop into the single digits, lower than previously examined.…”
Section: Effect Of Environmental Conditions On Community Compositionmentioning
confidence: 95%
See 2 more Smart Citations
“…Temperature is thought to influence phytoplankton species richness and diversity (Graham et al 2004), in part because temperature strongly influences the growth rates of individual species (Thomas et al 2012), including those in the genus Skeletonema. A comparison of growth rates under different temperatures revealed that cultures of S. marinoi grew faster than other Skeletonema species at the lowest tested temperatures (10 and 15°C) (Kaeriyama et al 2011). This could explain the dominance of S. marinoi in winter-spring samples, although wintertime temperatures in NBay drop into the single digits, lower than previously examined.…”
Section: Effect Of Environmental Conditions On Community Compositionmentioning
confidence: 95%
“…Rapid changes in species composition over a period of weeks could be due to stochastic effects. However, given the observation of physiological variation within the genus (Kaeriyama et al 2011), it is more likely that rapid compositional changes may indicate that diversification within the genus Skeletonema has led to species with finely tuned differences in their physiologies, allowing the genus to dominate the microplankton across a range of environmental conditions.…”
Section: Seasonal Variation In Skeletonema Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore applied the SSU rDNA analysis to 50 strains (27 from Osaka Bay and 23 from Tokyo Bay) of the 420 strains identified as S. dohrnii by LSU rDNA. In previous papers (Yamada et al 2010, Kaeriyama et al 2011) the name S. marinoi-dohrnii complex was used for this species, but S. sp. cf.…”
Section: Species Identificationmentioning
confidence: 99%
“…More recently, the application of molecular tools in taxonomy has revealed a large number of previously unrecognized species (e.g. Coleman 2001;Montresor et al 2003;Šlapeta et al 2005;Darling & WaDe 2008;EVans et al 2008), with potentially restricted geographical ranges (Pawlowski & Holzmann 2008) and niche breadths (De Vargas et al 1999;Lewis & FleChtner 2004;VanelslanDer et al 2009;Kaeriyama et al 2011). Sometimes, molecular evidence for lineage splitting has been backed up by breeding data and detailed morphological investigations.…”
Section: Introductionmentioning
confidence: 99%